Experimental Investigation of Electro-Discharge Face Grinding of Metal Matrix Composite (Al/SiC) - Yadav, Ram Singar; Singh, Gyan; Yadava, Vinod (Asian Review of Mechanical Engineering, 2019)
Surface quality and process productivity are the challenging performance measures in grinding of difficult-to machine materials these are measured in terms of Surface Roughness (Ra) and Material Removal Rate (MRR). Metal Matrix composites are the materials having aggregate properties of constituents like higher strength to weight ratio, toughness, stiffness and hardness. Because of having these superior properties MMCs are highly desirable in applications ranging from commercial aircraft to sports equipment but still facing challenges in machining of MMCs. Machining of MMCs by conventional machining process results poor surface finish and frequent tool failure due to presence of ceramic particles. Grinding of MMCs by conventional grinding process produces poor surface finish and low material removal rate due to frequent wheel loading. Electro-Discharge Face Grinding (EDFG) process is used on work specimen of the material Al/SiC MMC to investigate the effects of Wheel speed, Gap current, Pulse on-time and Pulse off-time on Surface Roughness (Ra) and Material Removal Rate (MRR). Surface Roughness (Ra) increases with increase in Wheel RPM, Gap current and Pulse on-time. MRR also increases with increase in Gap current and Pulse on-time while it is almost constant on increasing Wheel RPM. SEM micrograph of machined surface is taken for analysis of surface texture.